2021
DOI: 10.3390/foods11010056
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Change in Iron Content of Vegetables and Legumes in Australia: A Scoping Review

Abstract: Studies in UK and US have reported a temporal decline in the iron content of plant-based foods. Limited research on this topic has been conducted in Australia. The aim of this scoping review was to provide a comprehensive evaluation on the temporal change in iron content of Australian vegetables and legumes from 1900 onward. A systematic search of electronic databases, websites, backward reference searching, and Australian food composition tables was conducted. A total of 34 articles and six versions of Austra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
(55 reference statements)
2
4
0
Order By: Relevance
“…However, in our current research, Fe content in beans was 3.72 mg/100 g, while Cabrera et al [18] determined almost two times higher Fe content of 6.25 mg/100 g. Similarly, in the case of Zn, they [18] found almost a 100% higher level of Zn in beans (3.97 mg/100 g) than in our study (1.91 mg/ 100 g). These results might be in accordance with the findings of Eberl et al [19], who stated that studies in the UK and the US have reported a temporal decline in the Fe content of plant-based foods. They found significant decreases in Fe content in legumes, with higher and more variable values reported pre-2000 compared to recent years [19].…”
Section: Micromineralssupporting
confidence: 93%
See 1 more Smart Citation
“…However, in our current research, Fe content in beans was 3.72 mg/100 g, while Cabrera et al [18] determined almost two times higher Fe content of 6.25 mg/100 g. Similarly, in the case of Zn, they [18] found almost a 100% higher level of Zn in beans (3.97 mg/100 g) than in our study (1.91 mg/ 100 g). These results might be in accordance with the findings of Eberl et al [19], who stated that studies in the UK and the US have reported a temporal decline in the Fe content of plant-based foods. They found significant decreases in Fe content in legumes, with higher and more variable values reported pre-2000 compared to recent years [19].…”
Section: Micromineralssupporting
confidence: 93%
“…These results might be in accordance with the findings of Eberl et al [19], who stated that studies in the UK and the US have reported a temporal decline in the Fe content of plant-based foods. They found significant decreases in Fe content in legumes, with higher and more variable values reported pre-2000 compared to recent years [19]. However, Cabrera et al [18] noted similar to ours Fe concentration in sunflower seeds, i.e., 4.09 mg/100 g. Manganese levels varied between each analyzed group, with the highest values noted for soybean (2.21 mg/100 g) among legumes, and poppy seeds (7.2 mg/100 g).…”
Section: Micromineralssupporting
confidence: 93%
“…This discrepancy can be attributed to soaking the lentils, which leads to a decrease in NHI but was not performed here, and to the different cooking conditions. The plant-source mixture had a slightly higher iron content than the lentil mixture alone, because the lupin flour provides additional iron, as it has an iron content of 2.5–11.4 mg/100 g according to Eberl et al [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a systemic review of databases from Australia indicated a 30%‐50% decline in the iron content of vegetables. [ 64 ] A separate study assessed archived wheat grain samples collected from 1950 to 2016 and discovered an imbalance in carbohydrate/protein content after the 1960s. [ 65 ] Notably, uptrend increases in CO 2 and temperature were observed in the same time period, suggesting climate change may have impacted both yield and the nutritional content.…”
Section: Discussionmentioning
confidence: 99%